2021
DOI: 10.1007/s00270-021-03007-9
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Response on a Novel Fibrin-Based Coated Flow Diverter

Abstract: Purpose Due to thromboembolic complications and in-stent-stenosis after flow diverter (FD) treatment, the long-term use of dual antiplatelet treatment (DAPT) is mandatory. The tested nano-coating has been shown to reduce material thrombogenicity and promote endothelial cell proliferation in vitro. We compared the biocompatibility of coated (Derivo Heal) and non-coated (Derivo bare) FDs with DAPT in an animal model. Methods Derivo® bare (n = 10) and Derivo®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…9 Whether the heal coating affects aneurysm thrombosis has not yet been evaluated in detail, but a similar biocompatibility of the DERIVO 2heal to uncoated counterparts indicate a similar treatment efficacy. 7 In the presented case, the 5 mm large pseudoaneurysm was completely occluded within 5 days after treatment. Progressive aneurysm thrombosis might have been accelerated by SAPT compared to DAPT.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…9 Whether the heal coating affects aneurysm thrombosis has not yet been evaluated in detail, but a similar biocompatibility of the DERIVO 2heal to uncoated counterparts indicate a similar treatment efficacy. 7 In the presented case, the 5 mm large pseudoaneurysm was completely occluded within 5 days after treatment. Progressive aneurysm thrombosis might have been accelerated by SAPT compared to DAPT.…”
Section: Discussionmentioning
confidence: 57%
“…[4][5][6] These surface modifications mainly reduce platelet adhesion. 7 In a clinical study on the DED with BlueXide finishing under DAPT, the cumulative ischemic stroke rate was 3.4% and the morbidity rate was 1.7% at 1 year. 9 In a registry study, Taschner et al reported ischemic stroke in 4.2% and morbidity in 3.1%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations